Electrical and Financial Impacts of Inverter Clipping on Oversized Bifacial Photovoltaic Systems - Thunchanok Kaewnukultorn; Sergio Basilio Sepúlveda-Mora; Ryan Purnell; Steven Hegedus (Energies)
This paper studies the impacts of inverter clipping on bifacial PV modules under different weather and ground reflectivity. A 5 kW bifacial array was connected to a 3.8 kW grid-tied inverter, a 10 kWh Li-ion battery, and an EV charger. A PV output calculation model was developed to compare the estimated output of the modules with the actual measurements to evaluate the relation between ground reflectivity and clipping loss. The results showed that clipping potentially occurs on sunny days in summer from 10:00 to 15:00 during the period with the highest solar irradiance. Three colors of ground cover were also examined to compare the performance of bifacial modules under different albedo reflective properties. The results indicated that the white ground in winter leads to the highest bifacial gain (13.1%) and daily DC efficiency (22.2%) due to the combination of high reflectivity with low solar angle giving maximum upward reflection of direct sunlight. This same combination shows a minimal advantage in summer due to the clipping. The proposed model is evaluated, demonstrating 98.2% agreement between modeled and actual data for all conditions. Furthermore, simulation models based on the actual system with different system sizes and ground reflectivities have been studied to evaluate the impacts of the clipping in terms of technical losses and financial returns. The analysis shows that a high reflective ground condition can provide the best financial benefit, and the clipping loss does not have a great effect on the finance of the project since the loss is less than 4% of the annual production even in an extreme case.